Pengembangan Bahan Ajar Mata Kuliah Studi Implementasi Bagi Mahasiswa DIII Administrasi Negara FISH UNESA - Weni Rosdiana; Prasetyo Isbandono (Universitas Muhammadiyah Ponorogo, 2020)
The availability of reference books for implementation study courses varies with different study materials. The study program views the need for the availability of teaching materials for implementation study courses for students of the Diploma State Administration Unesa that support interaction in the learning process. The teaching material is in the form of an implementation study textbook that can support the achievement of learning objectives namely, at the end of the lecture students can understand and explain the ins and outs of the implementation study and its application effectively in public organizations. The purpose of writing this article is to describe the stages of the preparation of implementation study textbooks. The study was conducted using descriptive research with a qualitative approach. The results of the study describe the stages of preparing the implementation study textbook using the ADDIE Development Model which includes; Analysis Phase, Design Stage, Development Phase, Implementation Stage and Evaluation Stage. The quality of the feasibility of the content of the implementation study textbook still needs to add examples of cases that are relevant to the subject of policy implementation so as to make it easier for readers to understand the content of the implementation study textbook